On Nonlinear Simulation Methods and Tools for Evaluating the Performance of Ships and Offshore Structures in Waves - Shukui Liu; Apostolos Papanikolaou (Journal of Applied Mathematics)
This paper describes the development of alternative time domain numerical simulation methods for predicting large amplitude motions of ships and floating structures in response to incoming waves in the frame of potential theory. The developed alternative set of time domain methods simulate the hydrodynamic forces acting on ships advancing in waves with constant speed. For motions’ simulation, the diffraction forces and radiation forces are calculated up to the mean wetted surface, while the Froude-Krylov forces and hydrostatic restoring forces are calculated up to the undisturbed incident wave surface in case of large incident wave amplitude. This enables the study of the above waterline hull form effect. Characteristic case studies on simulating the hydrodynamic forces and motions of standard type of ships have been conducted for validation purpose. Good agreement with other numerical codes and experimental data has been observed. Furthermore, the added resistance of ships in waves can be calculated by the presented methods. This capability supports the increased demand of this type of tools for the proper selection of engine/propulsion systems accounting for ship’s performance in realistic sea conditions, or when optimizing ship’s sailing route for minimum fuel consumption and toxic gas emissions.